2018
DOI: 10.1016/j.cmi.2017.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin for acute lower respiratory tract infection in primary care: subgroup analysis by bacterial and viral aetiology

Abstract: Amoxicillin may reduce the risk of illness deterioration in patients with a combined bacterial and viral infection. We found no clinically meaningful benefit from amoxicillin treatment in other subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
19
2
Order By: Relevance
“…The reasons for reduced reconsultation rates are unclear, but one suggestion is that if a prescription is delayed, by the time the antibiotic course has finished, symptoms will have had more time to settle and so reconsultation is less likely; or it could be that secondary opportunistic bacterial infections that start later after an initial viral illness are more effectively managed by the later start of a delayed prescription. The second suggestion is supported by findings from the large GRACE trial; one of the groups that reported beneficial effects for antibiotics were people for whom evidence was found of coinfection with viruses and bacterial pathogens 60…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The reasons for reduced reconsultation rates are unclear, but one suggestion is that if a prescription is delayed, by the time the antibiotic course has finished, symptoms will have had more time to settle and so reconsultation is less likely; or it could be that secondary opportunistic bacterial infections that start later after an initial viral illness are more effectively managed by the later start of a delayed prescription. The second suggestion is supported by findings from the large GRACE trial; one of the groups that reported beneficial effects for antibiotics were people for whom evidence was found of coinfection with viruses and bacterial pathogens 60…”
Section: Discussionmentioning
confidence: 96%
“…The second suggestion is supported by findings from the large GRACE trial; one of the groups that reported beneficial effects for antibiotics were people for whom evidence was found of coinfection with viruses and bacterial pathogens. 60 …”
Section: Discussionmentioning
confidence: 99%
“…Use of signs and symptoms of disease to rule out acute Q fever would be most appropriate in patients with nonsevere lower respiratory tract infections, i.e., in cases where pneumonia is not suspected clinically. In such cases, use of antibiotics has been shown to provide little benefit in primary care, both overall and in patients aged 60 years and above, but may cause slight harms [25,26]. Nevertheless, inappropriate use of antibiotics remains common in this population, as a study performed in 14, 987 outpatients was recently able to show [27].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, use of antibiotics has been shown to provide little bene t in primary care, both overall and in patients aged 60 years and above, but may cause slight harms. [25,26] Nevertheless, inappropriate use of antibiotics remains common in this population, as a study performed in 14987 outpatients was recently able to show. [27] In a subgroup of 3306 patients with laboratory-con rmed in uenza, in whom no pneumonia had been diagnosed, 945 (29%) were prescribed an antibiotic.…”
Section: Discussionmentioning
confidence: 99%